Globalization perspectives from central and eastern Europe - Fábián, Katalin (Emerald, 2007)
Globalization studies are rapidly filling many a library shelf, and understandably so. The geographical shift in contemporary history towards a more global world is not only significant in its own right, but also interrelates closely with other principal social changes concurrently unfolding, for example, in respect of economy, governance, identity and knowledge. As a result, research built around a theme of globalization offers among the most promising avenues to develop a wide-ranging coherent systemic perspective on societal trends today. Hence, the present book on globalization in Central and Eastern Europe (CEE) is especially welcome.Between these covers specialists on these countries researchers who are moreover mostly born of the region itself offer probing examinations of the intersections of transplanetary relations with cultural, ecological, economic, historical, political and psychological circumstances particular to this part of the world. The authors thereby adeptly put into practice the so-called glocalization principle that globality is never divorced from the particular place of its expression. Collectively, the chapters make an important inroad into deficits in globalization research regarding Central and Eastern Europe. Some other area studies research is published with an eye-catching reference to globalization in the title but actually says little on that subject. Not so here.This book does consistently and carefully address issues of growing transplanetary connectivity, effectively teasing out connections between globalization, regionalization and national experiences in CEE. Moreover, by accepting the challenge of publishing in English the researchers make their accounts more available to readers beyond the countries concerned. Having made this generous overture, it is for globalization generalists, as well as specialists on globalization in other parts of the world, to grasp the opportunity to digest the work presented here and make warranted adjustments to their understandings. Contemporary Studies in Economic and Financial Analysis is now available online at ScienceDirect full-text online of volumes 85 onwards.
Keywords: Business & Economics -- Econometrics.; Political Science -- Globalization.; Globalization.; Econometrics.; elektronické knihy; electronic books